2020
DOI: 10.1021/acs.biomac.0c00362
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Near-Infrared Fluorescent Proteins by Packaging in Virus-like Particles

Abstract: Near-IR fluorescent Qβ virus-like particles (VLPs) were produced in a high yield by packaging highly red-shifted monomeric and dimeric versions of biliverdin-dependent fluorescent proteins within the capsid shell. The simple addition of biliverdin hydrochloride to the medium during or after Escherichia coli protein expression was enough to produce fully matured encapsidated fluorophores. The packaged near-IR proteins exhibited identical photochemical properties to their nonencapsidated analogues but were far m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Three enzymes were tested with this system, and it was shown that the average number of encapsulated cargos could be somewhat controlled by modifying expression conditions, achieving a variable loading of PepE, a 24 kDa enzyme, between 2 and 18 copies per particle. This encapsulation strategy was also used to package fluorescent proteins (FPs) separately into Qβ VLPs, with up to 15 proteins per particle (Rhee et al, 2011), and near-infrared FPs with either 5 or 9 copies per particle (Das et al, 2020a).…”
Section: Nucleic Acidmentioning
confidence: 99%
“…Three enzymes were tested with this system, and it was shown that the average number of encapsulated cargos could be somewhat controlled by modifying expression conditions, achieving a variable loading of PepE, a 24 kDa enzyme, between 2 and 18 copies per particle. This encapsulation strategy was also used to package fluorescent proteins (FPs) separately into Qβ VLPs, with up to 15 proteins per particle (Rhee et al, 2011), and near-infrared FPs with either 5 or 9 copies per particle (Das et al, 2020a).…”
Section: Nucleic Acidmentioning
confidence: 99%
“…All of the samples were prepared at a concentration of 100 μg mL −1 in PBS in the presence of 1 μM rapamycin. Resonance frequencies were measured simultaneously at seven harmonics (5,15,25,35,45,55,and 65 MHz). For clarity, only the frequency of the fifth overtone is shown.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Protein cage nanoparticles are protein-based supramolecules that have spherical and hollow architectures with highly symmetric structures and uniform sizes. The spherical hollow structures of protein cage nanoparticles provide two distinct spaces: the interior space and the exterior surface. , The interior spaces of protein cage nanoparticles have been widely used as size-constrained nanoreactors for the synthesis of biomimetic nanomaterials, as well as cargo containers for the targeted delivery of diagnostics and/or therapeutics and the sequestered cascade reactions of multiple enzymes. Small cargo molecules generally pass through the pores of protein cage nanoparticles. However, large cargo molecules and enzymes are generally too big to pass through the pores. Therefore, they have been generally encapsulated through either the in vitro disassembly/reassembly process of protein cage nanoparticles with cargo molecules or the coassembly of protein cage nanoparticles and cargo molecules mediated by selective interactions between protein cage subunits and cargo molecules in bacteria. …”
Section: Introductionmentioning
confidence: 99%
“…They are widespread in nature and display diverse morphologies and functions, with viral capsids and ferritin being among the most well-known examples (1). Natural protein cages have been functionalized for potential uses across biotechnology and medicine including as nanoreactors (2)(3)(4), building blocks to construct nanomaterials (5,6), and display/delivery vehicles (7)(8)(9). Their broad prospects have inspired construction of synthetic equivalents using engineered protein building blocks that do not assemble into cage-like structures in the naturally occurring state (10).…”
Section: Introductionmentioning
confidence: 99%